2003
DOI: 10.1046/j.1475-1313.2003.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gestational nicotine treatment on newborn rat retina: a histopathological and morphometric analysis

Abstract: Gestational nicotine treatment induces marked changes in the organisation of the developing retina in newborn rats histopathologically. Quantitative morphometric analysis clearly demonstrated that the two most affected structures were the retinal ganglion cells and the inner plexiform layer, both of which are supplied by central retinal artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
(40 reference statements)
3
14
1
6
Order By: Relevance
“…The posterior lens capsule does not have this layer and appears smooth and thin. The migration of the lens epithelial cells over the posterior lens capsule behind the equator is responsible for the formation of posterior subcapsular cataract [9]. In the present study prenatal isotretinoin treatment during day 12-18 showed similar findings in many rats.…”
Section: Discussionsupporting
confidence: 82%
“…The posterior lens capsule does not have this layer and appears smooth and thin. The migration of the lens epithelial cells over the posterior lens capsule behind the equator is responsible for the formation of posterior subcapsular cataract [9]. In the present study prenatal isotretinoin treatment during day 12-18 showed similar findings in many rats.…”
Section: Discussionsupporting
confidence: 82%
“…15 This enhancement of the antihypoxia defence system because of excessive intrauterine hypoxia is speculated to be another possible mechanism that reduces the incidence of severe ROP. Recent reports demonstrated an increase in haemeoxygenase 1 and 2 expressions in the placenta of smoking mothers, and increased levels of ceruloplasmin in the plasma of newborns and mothers exposed to tobacco smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed using New Zealand white albino rabbits weighing between 3.0 and 3.5 kg, and experiments were conducted in accordance with the ARVO Statement for the Use of Animals in Ophthalmic and Vision Research [15,16,17]. The rabbits were randomly divided into four groups, and each group consisted of 10 eyes of 10 rabbits.…”
Section: Methodsmentioning
confidence: 99%